Pathomorphological changes of the placenta in coronavirus disease (COVID-19) in pregnant women in the second and third trimesters of pregnancy - Savchuk, T.V. (Medicni Perspektivi, 2024)
Despite the severity of the course of COVID-19 in pregnant women, COVID-19 remains a risk factor for perinatal losses. The aim of the study was to determine the pathomorphological changes in the placenta in pregnant women with COVID-19 during the second and third trimesters of gestation in cases of live birth and antenatal fetal asphyxia. Placentas of pregnant women with COVID-19 were examined: in cases of live birth (n=122; Group I), in cases of antenatal fetal asphyxia (n=27; Group II), and in a comparison group (n=40). Macroscopic, microscopic, immunohistochemical, morphometric, and statistical methods were used. Subgroups: I.1 (n=49) – COVID-19 in the mother at 19-34 weeks of gestation and I.2 (n=34) – at 35-40 weeks. Placentas in antenatal fetal asphyxia, depending on the duration of the post-COVID interval (the time interval from the diagnosis of COVID-19 to delivery), were divided into subgroups – II.1 (n=8) and II.2 (n=19). In subgroup II.1, the post-COVID interval was 5-17 weeks; in II.2 – 1-4 weeks. In the acute phase of the disease, placentas predominantly showed congestion, thrombosis, hemorrhages, and placentitis – 100% (95% CI: 94.5%-100%). An increase in the number of syncytial nodules was found in subgroup I.2: 12.7 [11; 14] compared to 5.8 [5; 7] in the control group, p<0.0001. A decrease in the number of terminal villi was observed in subgroups I.1 and II.1 – 16.3 [10; 25]; 10.3 [8; 12] respectively; p<0.0001, compared to 25.4 [20; 30] in the comparison group. All cases of COVID-19 in the mother were accompanied by edema of the stromal tissue of the terminal villi of the chorion, which led to a decrease in the percentage of blood vessels in the terminal villi: in subgroup I.2 – 29.4 [25.6; 34.2]; II.1 – 16.5 [10.34; 24.37], and II.2 – 14.71 [10.1; 19.4] compared to 67.6 [58.78; 73.7] in the comparison group; p<0.0001. Proliferative changes in the wall of arterioles with subsequent arteriosclerosis were observed exclusively in subgroups I.1 and II.1 – 28.6% (95% CI: 16.6%-42.3%) and 100% (95% CI: 78.6%-100%) respectively. Pathomorphological changes in the placenta in COVID-19 during pregnancy are associated with the timing of infection and the phases of the inflammatory process, with an increase in the duration of the post-COVID interval – exudation (placentitis, edema of chorionic villi), proliferation followed by fibrosis. Factors that disrupt placental perfusion in the acute phase of COVID-19 include edema of the villous stroma, narrowing of the capillary lumen in the terminal chorionic villi, and the intervillous space. Compensatory mechanisms of the mature placenta include the appearance of a large number of syncytial bridges to increase the intervillous space and focal inflammation. Arteriolosclerosis, obliteration of the intervillous space, and hypoplasia of the terminal villi caused by SARS-CoV-2 damage to stem and semi-stem villi during COVID-19 in the second trimester of pregnancy are mechanisms of chronic placental insufficiency and a risk factor for intrauterine fetal hypoxia.